PENGARUH KOMPENSASI, LINGKUNGAN KERJA DAN PENGAWASAN TERHADAP SEMANGAT KERJA KARYAWAN BAGIAN PRODUKSI PADA PT. TIRTA SARI SURYA RENGAT - Wahyu Ningsih; Machasin '; Ahmad Rifqi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study to analyzed the extent of the effect of compensation, work environment and supervision of morale on PT.Tirta Sari Surya Rengat.While the techniques of data analysis in this study the authors used quantitative descriptive method with the help of SPSS (statistical package of social science). Based on the results of data analysis known that compensation, work environment and supervision significant effect on employeed morale in the production of PT. Tirta Sari Surya Rengat. The third independent variable is the dominant influencedeither partially nor simultaneously on employee morale at PT. Tirta Sari Surya Rengat.Based on these results the authors suggest for the company to pay attention to the success of compensation as wages / salaries, incentives, benefits, social security, leave, and give rewards to employees who are competent, and able to create a comfortable working atmosphere. Other contributing factors to be aware of the company is working environment such as working environment, cleanliness of the workplace, tools memadahi work equipment, the atmosphere of the work area, as well as oversight of the work such as setting a standard size work, measuring the implementation of activities, benchmarking implementation of the standard deviation analysis and taking corrective action so that employees are more eager to run the job in order to realized a positive productivity PT.Tirta Sari Surya Rengat.Keywords: Compensation, Work Environment, Supervisionand, morale employee